Detection of some virulence enzymes of Malassezia spp. isolated from patients of Pityriasis Versicolor and their sensitivity to some antifungal agents. - Abeer Takleef Noor; Ali A Alsudani (Al-Qadisiyah Journal of Pure Science, 2020)
This study included isolation and identification of Malassezia spp. from patients of Pityriasis Versicolor (PV) diagnosis by the dermatological consultant at Al-Diwaniyah Teaching Hospital for the period from 1/10/2019 to 5/3/2020, and detection of the virulence enzymes of these species and their sensitivity to some antifungal agents. 87 specimens were collected (38 females 43.7%, and 49 males 56.3%). 73 specimens (84%) were positive while 14 specimens (16%) were negative to direct and indirect examination. The results of isolation and identification of Malassezia spp. based on direct examination of specimens with KOH10%, indirect methods of growing specimens on SDA medium, and biochemical tests showed that the most occurrence isolates is M. furfur with 30 isolates (34.4%) followed by M. globosa with 22 isolates (25.2%), then M. slooffiae with 16 isolates (18.3%), and M. pachydermatis with 5 isolates (5.7%), while 14 specimens (16.0%) that did not give positive growth. The results also showed the ability of some species to produce protease enzyme, the rates of transparent halo diameters around the colonies on the skimmed milk medium ranged from (9.66-11.66) mm, and M. pachydermatis showed the highest ability to produce lipase enzyme with a precipitation diameter (24 mm), followed by M. furfur (20.33 mm), M. globosa (15 mm), then M. slooffiae (13.3 mm), also M. pachydermatis showed the highest ability to produce hemolysin enzyme with a degradation zone diameter. (18.33 mm), followed by M. furfur (17.33 mm), M. slooffiae (13 mm), and M. globosa (11 mm). The antifungal sensitivity of Malassezia spp. was tested using eight tablet, the results showed that the Ketoconazole is the most effective in inhibiting the growth of the fungal species compared to other antifungals agents, as the average diameter of the inhibition zone was (46.66 mm) for M. globosa, which is the highest rate of inhibition compared with other species, followed by M. furfur (45.33 mm), M. slooffiae (43.66 mm), M. pachydermatis (38.66 mm), followed by the antifungal Fluconazole with an inhibition diameter (35.66 mm) for M. furfur, followed by M. slooffiae (33.33 mm), M. pachydermatis (33 mm) and M. globosa (20 mm), while Nystatin showed no effect on the growth of Malassezia spp.